Accuracy of staging laparoscopy in detecting peritoneal dissemination in patients with gastroesophageal adenocarcinoma. Issue 3 (10th March 2015) - Simon, M.; Mal, F.; Perniceni, T.; Ferraz, J.‐M.; Strauss, C.; Levard, H.; Louvet, C.; Fuks, D.; Gayet, B.
Summary: Despite staging laparoscopy (SL) with peritoneal lavage is recommended in US Guidelines in patients with potentially resectable gastroesophageal adenocarcinoma, this procedure is not systematically proposed in French Guidelines. Therefore, we decided to analyze the results of systematic SL in patients considered for preoperative chemotherapy. From 2005 to 2011, 116 consecutive patients with distal esophagus, esogastric junction, and gastric adenocarcinoma ≥T3 or N+ without detectable metastatic dissemination by computed tomography (CT) scan imaging underwent SL before neoadjuvant chemotherapy. Positive and negative SLs were compared according to tumor characteristics. SL was positive in 15 cases (12.9%) including 14 with peritoneal seeding (localized in five, diffuse in nine). SL was positive in 7 (24.1%) of 29 patients with poorly differentiated tumor, in 9 (32.1%) of 28 patients with signet ring cells, in 7 (50%) of 14 patients with gastric linitis tumor, and in 15 (16.3%) of 92 patients with T3 or T4 tumor. All the lesions of distal esophagus extending to the cardia had a negative SL. Among the 14 patients with peritoneal carcinomatosis at SL, nine (65%) had signs of peritoneal seeding on initial CT scan. One (0.8%) patient had a small bowel perforation closed laparoscopically. If systematic SL before preoperative chemotherapy does not seem justified because of its low accuracy, it should be performed in patients with poorly differentiated tumor, signet ring cell, and gastric linitis plastica components on biopsy and when CT scan is suggestive of T4 tumor, ascites, or peritoneal nodule.